Rola języka polskiego w trwaniu i odradzaniu się kultury Polaków w niepodległej Ukrainie - Ustrzycki, Adam Tadeusz (Acta Polono-Ruthenica, 2008)
This article aims to describe the function played by Polish language In the life of Poles residing in independent Ukraine. The hypothesis on the lack of necessity to use a native language in everyday life in order to preserve cultural distinctness has been verified during the field-research conducted by the author. Polish language is only one of the elements of widely-understood Polish culture. The group subject to field-research study has also preserved other elements, such as: hierarchy of values of norms and patterns, feeling of distinctiveness, typical Polish traditions and customs. This observation contrasts with stereotypical opinion according to which preservation of culture is impossible without preservation of language.